Arguing for a citizens basic income: a contribution from a feminist economics perspective - McKay, Ailsa (2000)
Current debates concerning the future of social security provision in advanced capitalist states have raised a citizens‟ basic income (CBI) as a possible reform package. The proposal is based on the principles of individuality, universality and unconditionality and ensures a minimum income guarantee for all members of society. Implementing a CBI, thus, entails radical reform of existing patterns of welfare delivery and would bring into question the institutionalized relationship between work and welfare, upon which modern welfare states are premised. It follows that the practice of arguing for a CBI has tended to concentrate on issues regarding the role of the state in providing income security for all citizens and, in particular, to issues pertaining to the world of paid work. However such a concentration indicates bias in the approach to study and serves to confine the welfare reform agenda. The purpose of this thesis is to make a positive contribution to the CBI literature by examining the proposal from a feminist economics perspective. It is argued that a CBI has the potential to promote equal rights of freedom for men and women and provides the basis for the development and sustainability of new and liberating patterns of working and living. However, this particular aspect of the proposal will never be fully considered as long as the analytical framework employed is dominated by an adherence to neo-classical economic theory. Embracing a feminist economics perspective allows for the identification of the androcentric bias inherent within the neo-classical construct and further provides an alternative methodological approach that serves to open up the debate to incorporate a more realistic vision of the nature of modern socio-economic relationships.